Public Speaking Clinic for Tour Guides: A Community Service Program in Matano Iniaku Tourism Village in Collaboration with PT. Dialogika Pesona Indonesia - Asrofi, Muhammad Ghufran; Nirsal, Nirsal; Nurfalaq, Aryadi; Naim, Muhammad; Kaswar, Andi Baso; Idkhan, Andi Muhammad (MEKONGGA: Jurnal Pengabdian Masyarakat, 2025)
The main problem faced by the partner, namely the Matano Iniaku tourism management group in Matano Tourism Village, is the low communication ability and public speaking skills of tour guides in delivering information about tourist destinations in an engaging and persuasive manner. To address this issue, a Public Speaking Clinic was conducted to improve participants’ speaking abilities, build self-confidence, and enhance their storytelling techniques. The program was implemented using an experiential learning approach through interactive training, hands-on practice, presentation simulations, and mentoring by professional trainers from PT. Dialogika Pesona Indonesia. The two-day activity was attended by 19 participants consisting of tour guides and destination managers. The evaluation results showed a 93% increase in communication skills, particularly in articulation, intonation, message structure, and nonverbal expression. This program has provided a tangible solution for partners in improving tourism service quality and can serve as a model for communication competency development in the local tourism sector.